NMR study on the stabilization and chiral discrimination of sulforaphane enantiomers and analogues by cyclodextrins - Recio, Rocío (2018)
Sulforaphane (SFN), a phytochemical isolated from broccoli, is an important antitumoral compound with additional beneficial effect on other important diseases. However, the chemical instability of SFN has hampered its clinical use. In order to circumvent this problem, we report the first comparative study on the inclusion complexes of SFN and SFN homologues with different cyclodextrins by NMR spectroscopy. From this study it has been shown that α-CD is the most indicated cyclodextrin for the stabilization of SFN and SFN homologues, and that the highest affinity constant is that of the isothiocyanate obtained from the wasabi. Furthermore, the study of the inclusion complexes of α-CD and the non-natural SFN and analogues with S absolute configuration at sulfur shows for the first time that α-CD is able to discriminate between the two enantiomers, with the natural R enantiomers forming the inclusion complexes with higher affinity.